Meta-analysis of Icelandic and UK data sets identifies missense variants in SMO, IL11, COL11A1 and 13 more new loci associated with osteoarthritis - Styrkarsdottir, Unnur; Lund, Sigrun H.; Thorleifsson, Gudmar; Zink, Florian; Stefansson, Olafur A.; Sigurdsson, Jon K.; Juliusson, Kristinn; Bjarnadottir, Kristbjörg; Sigurbjornsdottir, Sara; Jonsson, Stefan; Norland, Kristjan; Stefansdottir, Lilja; et al. (Nature genetics, 2018)
Osteoarthritis has a highly negative impact on quality of life because of the associated pain and loss of joint function. Here we describe the largest meta-analysis so far of osteoarthritis of the hip and the knee in samples from Iceland and the UK Biobank (including 17,151 hip osteoarthritis patients, 23,877 knee osteoarthritis patients, and more than 562,000 controls). We found 23 independent associations at 22 loci in the additive meta-analyses, of which 16 of the loci were novel: 12 for hip and 4 for knee osteoarthritis. Two associations are between rare or low-frequency missense variants and hip osteoarthritis, affecting the genes SMO (rs143083812, frequency 0.11%, odds ratio (OR) = 2.8, P = 7.9 × 10 −12 , p.Arg173Cys) and IL11 (rs4252548, frequency 2.08%, OR = 1.30, P = 2.1 × 10 −11 , p.Arg112His). A common missense variant in the COL11A1 gene also associates with hip osteoarthritis (rs3753841, frequency 61%, P = 5.2 × 10 –10 , OR = 1.08, p.Pro1284Leu). In addition, using a recessive model, we confirm an association between hip osteoarthritis and a variant of CHADL 1 (rs117018441, P = 1.8 × 10 −25 , OR = 5.9). Furthermore, we observe a complex relationship between height and risk of osteoarthritis. Genome-wide association meta-analysis of data sets from Iceland and the UK identifies 16 new risk loci for osteoarthritis, including missense variants in SMO , IL11 , and COL11A1 .